Paraneoplastic neurological syndrome: focus on the involvement of the peripheral nervous system - Sitkali I.V. (Саратовский научно-медицинский журнал, 2017)
The information about epidemiology, pathogenesis and clinical heterogeneity of paraneoplastic neurological syndrome is summarized and based on Russian and foreign literature. The main attention is devoted to the affection of peripheral nervous systems in patients with oncological diseases. We report the information about anti-neuronal antibodies associated with paraneoplastic syndrome. The diagnostic criteria of paraneoplastic neurological syndromes are presented.